Induction of immunogenic cell death by active components of natural products reshaping the tumor microenvironment for enhanced antitumor immunity - Chen, Xiaojie; Li, Haojia; Chen, Jianfei; Hou, Boyang; Tian, Zhaokun; Qiu, Wenyan; Yu, Zhiyong (Frontiers in Pharmacology, 2026)
BackgroundThe immunosuppressive tumor microenvironment (TME) is a principal factor limiting the success of current cancer immunotherapies. Immunogenic cell death (ICD), a process whereby dying tumor cells elicit an adaptive immune response through the emission of damage-associated molecular patterns (DAMPs), offers a promising strategy to counteract this limitation. Natural products (NPs) constitute a valuable reservoir of compounds capable of triggering ICD.PurposeThis review aims to provide a comprehensive overview of ICD inducers derived from NPs, detail their molecular mechanisms of action, and explore their capacity to remodel the immunosuppressive TME.MethodsWe performed a comprehensive literature search in relevant electronic databases to identify studies describing NPs-based components that stimulate characteristic ICD markers, such as surface exposure of calreticulin (CRT), and extracellular release of ATP and high mobility group box 1 (HMGB1).ResultsActive components of NPs were demonstrated to initiate ICD largely via the induction of endoplasmic reticulum (ER) stress and reactive oxygen species (ROS). The consequent emission of DAMPs facilitates dendritic cell-mediated phagocytosis of tumor antigens and the priming of cytotoxic T lymphocytes. Additionally, the inflammatory milieu generated by NPs-induced ICD reprograms the TME by promoting the repolarization of macrophages to an immunostimulatory M1 phenotype and inhibiting the suppressive functions of myeloid-derived suppressor cells (MDSCs).ConclusionInducing ICD with NPs is a viable therapeutic strategy to potentiate anti-tumor immunity. The convergence of NPs-based ICD inducers with nanotechnology-based delivery systems offers a robust platform for the development of innovative combination regimens aimed at improving patient outcomes.